Incidence of Adverse Events Related to Therapies with sodium iodine (131I): Contribution to the Pharmacovigilance in Brazil - Jaqueline Cardena Fernandes; Elaine Bortoleti de Araújo; Adriana Iozzi Joaquim (Brazilian Journal of Radiation Sciences, 2024)
Radiopharmaceuticals for therapeutic have been increasingly used for the treatment of various pathologies. Beta-emitting radionuclides stand out in this modality due to the physical characteristics of the emitted particle. Iodine-131 (131I) is an example of a beta-emitting radionuclide, applied in the production of radiopharmaceuticals such as sodium iodine (131I), which represents an excellent therapeutic modality in the treatment of differentiated thyroid carcinomas. As well as other therapeutic modalities, radionuclide therapy using radiopharmaceuticals can also cause adverse reactions. This study aimed to evaluate the incidence of possible adverse events related to therapy with sodium iodine (131I), and evaluate the correlation with the administered activities, obtaining unprecedented pharmacovigilance data related to the use of therapeutic radiopharmaceuticals in Brazil. A retrospective analysis of medical records was carried out with electronic patients’ data diagnosed with differentiated thyroid carcinoma and undergoing therapy with radioiodine. A total of 116 patients were recovered from January/2019 to April/2021 and 89 were included according to the inclusion criteria. Of the patients, 54.6% reported an adverse event after radioiodine therapy. The most frequent events were those related to the gastrointestinal tract and local irradiation, and it was possible to identify that there was an increased incidence of events in those patients who were treated with greater activities. Based on the results obtained, the present study demonstrated the presence of acute events related to therapy in the studied population and that the incidence of events was correlated with the activity prescribed.